Answer:
See below
Explanation:
Part A:
![(x+2)(x+3) = (x+2)(x-3) + y](https://img.qammunity.org/2021/formulas/mathematics/high-school/746184diw75m7s89u44y08cp8mu7ykvlxp.png)
Resolving Parenthesis
![x^2+3x+2x+6=x^2-3x-2x+6+y\\x^2+5x+6 = x^2-5x+6+y](https://img.qammunity.org/2021/formulas/mathematics/high-school/fzl6ggn0reh5qh7x0vcnkdrngqjfmvjzsu.png)
Subtracting
and 6 to both sides
![5x= -5x+y](https://img.qammunity.org/2021/formulas/mathematics/high-school/391up7mqnf4qdjh065ier5hiuz7d1rhqnu.png)
Adding 5x to both sides
![y = 5x+5x\\y = 10x](https://img.qammunity.org/2021/formulas/mathematics/high-school/clql8ifvwsb1q83jbqgp0gpmvgmaii2lu1.png)
Comparing it with
where m is the slope while b is the y-intercept
So,
Slope = m = 10
Y-intercept = b = 0
Part B:
![x = my+b](https://img.qammunity.org/2021/formulas/mathematics/high-school/voh03mesx8j24n76vce9ca7t1biw6rgrks.png)
Subtracting b to both sides
![my = x-b](https://img.qammunity.org/2021/formulas/mathematics/high-school/9d185twapx1lrpy8oi4shbn1rvrxe5gxd7.png)
Dividing both sides by m
![y = (x-b)/(m)\\ y = (x)/(m) - (b)/(m)](https://img.qammunity.org/2021/formulas/mathematics/high-school/f6t8woym8pucbt6ic8tgf24t8euj79uquy.png)
Comparing it with
where m is the slope while b is the y-intercept
So,
Slope = m =
![(1)/(m)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ji8m0en105sldmugqreztb2479bdrj84hh.png)
Y-intercept = b =
![-(b)/(m)](https://img.qammunity.org/2021/formulas/mathematics/high-school/kwue2zc2gqrco0njyt0gh34zjnqo8o6tpn.png)